A Practical Guide to Service Management : Insights from industry experts for uncovering, implementing, and improving service management practices /: Insights from industry experts for uncovering, implementing, and improving service management practices. (2023) - Sutherland, Keith D; Sheets, Lawrence J. "Butch"
No abstract available